Iluminación de la cancha de futbol del barrio divino niño uso tecnología led (2021)
The present work describes the stages of the lighting design of the soccer field located in the Divino Niño neighborhood of the city of Cúcuta, Norte de Santander, applying the latest trends in public lighting for sports fields that are being developed in the country as it is the technology type LED, the which demands that these designs be carried out by qualified personnel and the application of RETILAP, where the equipment used in the lighting system meets the minimum technical requirements and that the LED type luminaires used in the project have certified photometrics. The design is distributed in two main aspects that are: The design and calculation of the lighting system with LED technology. The design and calculation of the infrastructure for the lighting system with LED technology. Finally, the evaluation of the technical, economic, environmental, technological and social aspects of the project and its impact on the coexistence of citizens who make use of this sports unit was carried out.